Grain size of Quaternary sediments in the continental shelf-margin: implications for paleo-environment in the Northwestern South China Sea - Jiawang Ge; Qingping Li; Xiaoming Zhao; Weixin Pang; Qi Fan; Xiang Cheng; Xin Zhang (Frontiers in Marine Science, 2024)
Introduction The quantitative distribution of grain size of sediments could imply the hydrodynamic conditions as well as terrestrial material composition; and thus, it is indicative of sea-level fluctuations, regional sources and climate changes. The environmentally sensitive components extracted from grain size data serve as excellent indicators of the sedimentary environment and monsoon intensity. Material and methods The drilling data from the shelf margin of the northwestern Qiongdongnan Basin provide an excellent opportunity for studying hydrodynamics and climate change in the Quaternary South China Sea (SCS). The 49 obtained samples of Quaternary sediments are primarily composed of clay and silt, with a low sand content. The environmentally sensitive components are extracted from the sediment samples, based on multiple attempts including grain size-standard deviation, the end-member modelling analysis and the principal component factor analysis methods. Results The increased grain size as supplemented by ratios of rolling movement on the sediment probability accumulation curves indicate enhanced hydrodynamic conditions in the Quaternary northwestern SCS. The alternative indicators of the Quaternary East Asian monsoon are obtained after a comprehensive comparative analysis. The changes in the content of the grain size components of 5.21-6.72 μm and 27.4-35.3 μm are used as the proxy indicators for the Quaternary East Asian summer and winter monsoon of the NW-SCS, respectively. It is likely indicated that the East Asian winter monsoon remarkably strengthened since 1.3 Ma but reached its maximum intensity around 0.8 Ma. During this period, the magnitude of both climatic temperature and sea-level fluctuations are significant, thus, the coarse-grained component increased at falling or low sea-level stages. Discussion The grain size characteristics of the Quaternary shelf margin sediments are indicative of hydrodynamic conditions, source-sink systems and environmental monsoon climate changes in the northwestern SCS.